2014
DOI: 10.1002/dta.1611
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine and nor‐buprenorphine levels in head hair samples from former heroin users under Suboxone® treatment

Abstract: In the current study, buprenorphine (BUP) and its major metabolite, nor-buprenorphine (NBUP), were determined in hair samples from former heroin users following Suboxone® treatment. Hair samples from 36 subjects were analyzed. The drugs of interest were isolated from hair by solid-liquid extraction with methanol and were determined by liquid chromatography-mass spectrometry, using an electrospray ionization interface. The analytical parameters of the method (such as linearity, limits of quantification, recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
(59 reference statements)
0
6
1
Order By: Relevance
“…Another major approach of a TDM concept is the quantitative compliance controlling. The implementation of this aspect of TDM by hair testing is controversially discussed and mostly criticized, as there are only a few selected drugs showing a sufficient correlation between the concentration in hair and drug dosage . Mostly, no evidence for a linear relationship between dosage and drug concentration in hair has been found .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Another major approach of a TDM concept is the quantitative compliance controlling. The implementation of this aspect of TDM by hair testing is controversially discussed and mostly criticized, as there are only a few selected drugs showing a sufficient correlation between the concentration in hair and drug dosage . Mostly, no evidence for a linear relationship between dosage and drug concentration in hair has been found .…”
Section: Discussioncontrasting
confidence: 55%
“…The implementation of this aspect of TDM by hair testing is controversially discussed and mostly criticized, as there are only a few selected drugs showing a sufficient correlation between the concentration in hair and drug dosage. [25][26][27][28][29] Mostly, no evidence for a linear relationship between dosage and drug concentration in hair has been found. [30][31][32][33] In the present study no dose-response relationship was observed by correlating all concentration values to the selfdeclared administered dose.…”
Section: Methods Validationmentioning
confidence: 99%
“…26,30 However, this approach is time consuming (at least two MS2 cycles per m/z) and may miss numerous compounds presenting a weak intensity. NCE allows an adaptation of the collision energy according the mass of the ion.…”
Section: Applicationmentioning
confidence: 99%
“…Stepped NCE is often used in MS2 experiments to provide an appropriate fragmentation regardless molecule's mass. 26,30 However, this approach is time consuming (at least two MS2 cycles per m/z) and may miss numerous compounds presenting a weak intensity.…”
Section: Applicationmentioning
confidence: 99%
“…Because buprenorphine only partially binds the μ opioid receptor, the effects of this drug do not increase linearly with the dose and patients experience a “ceiling effect” as the activity of this drug plateaus above a certain concentration unlike the other opioid treatments. This ‘ceiling effect’ makes buprenorphine a safer choice than other full agonists at higher doses [ 26 ].…”
Section: Review Of Prenatal Opioid Abuse Treatment Optionsmentioning
confidence: 99%